WE6.1 A Sustainable Appendicectomy. (9th August 2022) - Boag, Katie; Ho, Timothy; Quyn, Aaron; Peckham-Cooper, Adam
Abstract: Background and Aim: Equipment consumption is the third largest contributor to the carbon footprint of surgery. Laparoscopic surgery is particularly resource intensive. The aim of this quality improvement project is to reduce the carbon footprint of laparoscopic appendicectomies performed at this high volume trust. Methods: The laparoscopic appendicectomy was process-mapped and carbon footprint calculations performed. Three areas of change were identified: elimination of single use gowns and drapes, elimination of peri-operative catheterisation, and rationalisation of the equipment tray from 119 to 49 items. A staff survey was used to identify practices and gain feedback on the proposed changes. Changes were implemented from January 2022. Surgeons are able to ask for a 'sustainable appendicectomy pathway' at team brief. Procedures were monitored for one week. Results: Survey feedback indicated 100% (n=19) supported the proposed changes. The interventions save an estimated 7.48kgCO2e and £25.1 per procedure. No extra equipment was required during the procedures monitored. Conclusions: The interventions are predicted to save annually 3.9TCO2e and £13, 081 in the approximately 500 appendicectomies performed in this trust, and can be extrapolated to many types of procedures. Support from all members of the operating department is vital to sustaining the momentum of interventions. Following initial positive results, changes were extended to only use reusable gowns in one of the CEPOD theatres which perform around 2400 procedures/year. This will lead to a saving of at least 6386 disposable gowns/year (1.43T of waste). Further plans within this trust are to make the 'sustainable appendicectomy pathway' an opt-out decision.